Synthesis and study of optically transparent benzguanamine oligomers with luminescent properties - Lebedev, Vladimir (Eastern-European Journal of Enterprise Technologies, 2016)
The study of the synthesis of transparent BF oligomers and polymers with luminescent properties, which is an important issue in terms of obtaining new optically transparent luminescent polymers with high operational and spectral properties was carried out. It is shown that modification of benzguanaminе oligomers by glycerol with a content of 20 wt %, allows obtaining materials with high lighttransmittance, low residual stress, shrinkage and water absorption and high physical–mechanical characteristics. At the same time, such an important characteristic of scintillation plastics as BAL, in the aforementioned materials is at level with the PS and PMMA – 40 – 60 to 50 cm – 200 cm. The basic spectral–luminescent properties of transparent oligomers and polymers were investigated. It is shown that they are characterized by the extinction coefficient of up to 9000–12000 and intensity of luminescence with the relative quantum yield of up to 10 % in the range of 360–365 nm. The resulting polymers may be used as the basis of highly transparent products, plastic scintillators and other materials of the optical-luminescent materials science.